Pengaruh Corporate Ability dan Strategi Integrated Marketing Communication terhadap Corporate Reputation dengan Product Involvement sebagai Variabel Moderasi - Nahrian, Lutfy Azhary; Nadia, Citra (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
This study aims to determine the effect of cooperate ability and integrated marketing communication strategy on corporate reputation moderated by product involvement. This research is classified as quantitative research which aims to test the specified hypothesis. Respondents in this study were employees at Astra Honda Motor companies and branches in the Jabodetabek area. The sampling technique is randome sampling, taking 100 employees as a sample. Research data were obtained through questionnaires distributed through G-Form. The data collected was then analyzed with Path analysis assisted by the Smart PLS application. Based on the test results, it is known that corporate ability and IMC have a significant positive effect on corporate reputation, and product involvement has not been able to moderate the relationship between corporate ability and IMC on corporate reputation. Based on these findings, it is expected that the Astra Honda Motor company can always pay attention to communication and develop its capabilities in depth regarding aspects and indicators to maintain corporate reputation.